Penentuan pola distribusi optimal menggunakan metode saving matrix untuk meningkatkan fleksibilitas pemesanan - Winny Andalia; Devie Oktarini; Siti Humairoh (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to obtain the most appropriate and optimal cosmetic shipping routes that can minimize transportation distribution costs, and determining the magnitude of distribution cost savings. The object of this research is the distribution of Wardah Cosmetics in Palembang, and the study uses 7 retailers in Palembang. Analysis of determining the distribution route using the Saving Matrix Method. The results of the approach through the Nearest Insert, Nearest Neighbor and Sweep get the smallest value of the route along 73.6 Km. The analyzing results by using Saving Matrix Method determine the distribution route which can be converted from D1, D2, D3, D4, D5, D6, D7 into D3, D5, D6, D7, D1, D2, D4. The original mileage of 129 kilometers can be reduced to 73.6 kilometers, which means the distance can be shortened or more efficient by 55.4 kilometers. Route changes the result in lower product distribution costs. Initial transportation costs were Rp. 1.196.850 per day and subsequently getting down to Rp. 662.115 per day. Thus, the distribution channel cost savings of Rp. 534.735 per day.